PEMBERDAYAAN ORANGTUA MELALUI KEGIATAN SEMINAR PARENTING PADA SEKOLAH DASAR SWASTA DI LAMPUNG - Apri Kurniasih; Jamiluddin Yacub; Khalimatul Khusna; Titin Nurhidayati (Universitas Al-Falah As-Sunniyah Kencong Jember, 2026)
Parental involvement in their child's education is a key factor in successful elementary school learning. However, many parents do not yet understand their strategic role in building effective home-school collaboration. This community service activity aimed to empower parents through parenting seminars at 4 private elementary schools in Lampung namely SD Alam Azzahra Way Jepara, SD Al-Qur’an Darurrohman Bandar Agung, SD Alam Pringsewu and SD Alam Metro which was attended by 195 parents. The implementation method used a service learning approach that included four stages: needs analysis, material development, interactive seminars, and reflection and evaluation through questionnaires. The results of the activity showed a significant increase in parents' understanding with an average increase of 28.4% in terms of communication patterns with teachers, home learning support, and the establishment of positive routines for children. Furthermore, parents demonstrated greater motivation to actively collaborate with the school. This activity concluded that parenting seminars can be an effective strategy in strengthening home-school partnerships, thereby supporting student growth and development and learning success.